Highly oriented Langmuir–Blodgett film of silver cuboctahedra as an effective matrix-free sample plate for surface-assisted laser desorption/ionization mass spectrometry. Issue 31 (25th July 2017) - Kuo, Tsung-Rong; Chen, Yin-Chien; Wang, Chiung-I.; Shen, Tzu-Hau; Wang, Hong-Yi; Pan, Xi-Yu; Wang, Di-Yan; Liou, Chien-Chung; Chang, Yi-Hsuan; Chen, Yi-Chia; Wu, Yueh-Hsiu; Liu, Yun-Ru; et al.
Abstract : Design of a sample plate to solve the sweet spot issue is the key to expand the applicability of SALDI MS. Abstract : The design of a homogeneous sample plate to solve the sweet heating spot issues is the key step to expand the applicability of surface-assisted laser desorption/ionization mass spectrometry (SALDI MS). Herein, large-scale and highly oriented Langmuir–Blodgett (LB) films of uniform silver nanocrystals have been fabricated as a highly efficient and matrix-free sample plate for SALDI MS. Three individual silver nanocrystals (cubes, cuboctahedra and octahedra) assembled LB films have been applied as the sample plates for glucose detection by SALDI MS without an additional matrix. The results show that the signal intensity, background noise, signal-to-noise ratio and reproducibility have been significantly improved using LB films as the sample plate in comparison with commercial matrixes of CHCA and DHB. In particular, a relative signal of 5.7% was obtained for LB films of silver cuboctahedra. The significant improvement in the SALDI MS measurement could be attributed to the homogenous dissipation of laser irradiation energy to create a large area of the sweet heating spot on well-oriented silver cuboctahedra-based LB film. This ready-to-use sample plate has the potential for widespread commercial applications in SALDI MS.